2019
DOI: 10.1111/mms.12654
|View full text |Cite
|
Sign up to set email alerts
|

Increased alertness behavior in Australian fur seals (Arctocephalus pusillus doriferus) at a high vessel traffic haul‐out site

Abstract: Vessel impacts on marine mammals are of growing concern, and marine mammals in urbanized marine environments are at particular risk of exposure. Port Phillip Bay (Victoria, Australia) is one such environment, in which Australian fur seals (AUFS; Arctocephalus pusillus doriferus) haul‐out to rest, yet little is known about the impacts of vessels on resting seals. We used remote camera traps to investigate the influence of vessel traffic on AUFS behavior at a nonbreeding haul‐out site. Environmental, temporal, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Likewise, urban Eurasian red squirrels demonstrated the ability to assess risk levels of various approaching objects (e.g., humans and conspecific decoys) and modulated their FID accordingly (Uchida et al, 2019(Uchida et al, , 2020. Finally, a study on Australian fur seals (Arctocephalus pusillus doriferus) found that seals modulated their alert response based on vessel type and whether or not vessels conformed with mandated approach distance thresholds-indicating that the seals learned the legal distance ships were able to approach (Speakman et al, 2020).…”
Section: Modulating Behaviormentioning
confidence: 99%
“…Likewise, urban Eurasian red squirrels demonstrated the ability to assess risk levels of various approaching objects (e.g., humans and conspecific decoys) and modulated their FID accordingly (Uchida et al, 2019(Uchida et al, , 2020. Finally, a study on Australian fur seals (Arctocephalus pusillus doriferus) found that seals modulated their alert response based on vessel type and whether or not vessels conformed with mandated approach distance thresholds-indicating that the seals learned the legal distance ships were able to approach (Speakman et al, 2020).…”
Section: Modulating Behaviormentioning
confidence: 99%
“…Likewise, urban Eurasian red squirrels demonstrated the ability to assess risk levels of various approaching objects (e.g., humans and conspecific decoys) and modulated their FID accordingly (Uchida et al, 2019(Uchida et al, , 2020. Finally, a study on Australian fur seals (Arctocephalus pusillus doriferus) found that seals modulated their alert response based on vessel type and whether or not vessels conformed with mandated approach distance thresholds-indicating that the seals learned the legal distance ships were able to approach (Speakman et al, 2020).…”
Section: Modulating Behaviormentioning
confidence: 99%